Trends in academic research on thirdhand smoke using bibliometric analysis - Joseph K. Ahialey; Yubin Lee; Myung-Bae Park; Jimi Huh (Tobacco Induced Diseases)
Introduction This study used quantitative analysis to explore the current landscape of thirdhand smoke (THS) research by identifying gaps and emerging trends. Despite growing evidence of health risks associated with THS, research remains sparse, and no public policies address THS exposure. This analysis aimed to inform future studies and policies, in order to mitigate THS-related health risks.